Facts on inhaled Insulin - Gowtham .T, Rafi khan .P, Gopi Chand .K, Nagasaraswathi. M (Journal of Applied Pharmaceutical Science)
Until today, diabetic patients who need insulin to manage their disease had only one way to treat their condition but Exubera is an inhaled powder form of recombinant human insulin (rDNA) for the treatment of adult patients with type 1 and type 2 diabetes. American and European Drug Agencies (FDA and EMEA) approved the first pulmonary delivered version of insulin (Exubera®) for diabetic patients and hope that the availability of inhaled insulin will offer more options to patients for better control of their blood sugars. The safety and efficacy of Exubera has been studied in approximately 2500 adult patients with type 1 and type 2 diabetes. In clinical studies, Exubera reached peak insulin concentration more quickly than some insulins, called regular insulin, administered by an injection. Side effects associated with Exubera therapy seen in clinical trials included cough, shortness of breath, sore throat, and dry mouth. Exubera is not to be used for the patients who smoke or if you recently quit smoking (within the last 6 months). Exubera is not recommended in patients with asthma, bronchitis or emphysema. The main objective of this review is to elucidate the advantages and adverse events of inhaled insulin.
Keywords: Asthma, Bronchitis, Emphysema, Exubera, inhaled insulin.